Biodiversity of Termites and Damage Building in Semarang, Indonesia - Subekti, Niken; Priyono, Bambang; Aisyah, Afrin Nur (Biosaintifika: Journal of Biology & Biology Education, 2018)
Termites cause a lot of damage and big losses for building components, especially those made of wood. High population growth and rapid infrastructure development in Semarang city affect the natural habitats of termites. This phenomenon changes the termites behavior of foraging in buildings. Semarang city has humidity, temperature, and altitude that allows termites to live and breed well. The purpose of this study was to determine the types of termites living in housing in Semarang city as well as the level of attacks on housing. This research was conducted in nine housing in Semarang City. The research was carried out with two methods: building inspection and wood-feeding method by using Pinus mercusii wood measures 2 cm x 2 cm x 46 cm. The results found four types of termites that attack wood feeds namely Macrotermes gilvus, Microtermes inspiratus, Odontotermes javanicus, Coptotermes curvignathus and Cryptotermes sp.. Based on interviews and building inspection, it was known that the condition of the building in the category of "moderate" was occupying the most position (74.44%), good (17.78%) and lightly damaged (7.78%). From the causes of damage to building components, it can be concluded that the level of termite attack against damage to recidential buildings in Semarang city 44.58%. Cross-tabulation analysis of Chi-Square shows that there is a correlation between age and treatment with damage to the building. Futher, the finding can be used as baseline information for further scientific investigation for effective termites control on residential building components.